Определение затрат времени при бурении съемным породоразрушающим инструментом - Онищин, В.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
One of the future trends towards improving the method for hand rock drilling should
become the development and introduction of retractable bits, which enable to reduce the time for
sinking/retrieval operation and the manpower as well as to improve the drilling rate. The design of
the retractable bits and the possibility of their application in combination with the wireline system
and other high wear resistant drill strings should become the cornerstone for drilling time
estimations.